Accounting Information Relevance for Investment Decision Making Processes (gjstudies, 2026)
This research investigates the evolving relevance of accounting information withincontemporary investment decision-making frameworks, challenging traditional assumptions about financial statement utility. We propose a novel methodologicalapproach that integrates behavioral finance constructs with computational textanalysis to examine how professional investors process, weight, and ultimately utilize accounting disclosures. Departing from conventional capital markets researchthat predominantly employs archival data and event studies, this study employsa mixed-methods design combining controlled laboratory experiments with investment professionals and natural language processing of investment committee transcripts. Our primary research question interrogates whether the informational content of accounting reports remains a primary input for equity valuation in an eracharacterized by alternative data sources, algorithmic trading, and shortened investment horizons. A secondary question explores the cognitive heuristics investorsemploy when encountering complex accounting disclosures, particularly those related to intangible assets and forward-looking estimates. The experimental component exposes 87 certified financial analysts to varying presentations of identicalaccounting information, manipulating narrative disclosure tone, footnote complexity, and non-GAAP metric prominence. Concurrently, we analyze 2,500 pages ofinvestment committee deliberations from three asset management firms using acustom dictionary to quantify references to traditional accounting metrics versusalternative data points. Results reveal a significant divergence between professedreliance on accounting fundamentals and actual decision weightings. While participants verbally affirmed the importance of earnings quality and balance sheetstrength, process tracing and transcript analysis indicate that accounting data oftenserves a confirmatory rather than formative role, particularly for growth-orientedinvestments. A striking finding is the increased cognitive discounting applied toaccounting information when accompanied by voluminous regulatory disclosures,suggesting an information overload effect that undermines relevance. Furthermore,we identify a ’narrative coherence heuristic,’ where investors place disproportionateweight on accounting disclosures that align with a pre-existing investment thesis,while discounting contradictory data. The study concludes that accounting relevance is not an inherent property of the information itself but emerges from theinteraction between disclosure design, investor cognitive architecture, and decisioncontext. This reconceptualization has profound implications for standard setters,corporate preparers, and the investment community, suggesting that enhancing relevance may require fundamental changes in disclosure philosophy and presentation,moving beyond incremental improvements to existing reporting models.